Antibody induced seizure susceptibility and impaired cognitive performance in a passive transfer rat model of autoimmune encephalitis - Pişkin, Şura Akat; Korkmaz, Hande Yüceer; Ulusoy, Canan Aysel; Şanlı, Elif; Küçükali, Cem Ismail; Onat, Filiz; Tüzün, Erdem; Çarçak, Nihan (Frontiers in Immunology, 2023)
Objective: Autoimmune encephalitis (AE) is a distinct neuro-immunological disorder associated with the production of autoantibodies against neuronal proteins responsible for pharmacoresistant seizures, cognitive decline and behavioral problems. To establish the causal link between leucinerich glioma inactivated 1 (LGI1) antibody and seizures, we developed an in-vivo antibodymediated AE rat model in which serum antibodies (IgG) obtained from blood samples of leucinerich glioma inactivated 1 (LGI1) protein antibody (IgG) positive encephalitis patients were passively transferred into non-epileptic Wistar rats. Serum IgG of N-methyl-d-aspartate receptor (NMDAR) antibody positive patients were used as positive control since the pathogenicity of this antibody has been previously shown in animal models.Methods: Total IgG obtained from the pooled sera of NMDAR and LGI1-IgG positive patients with epileptic seizures and healthy subjects was applied chronically every other day for 11 days into the cerebral lateral ventricle. Spontaneous seizure development was followed by electroencephalography. Behavioral tests for memory and locomotor activity were applied before and after the antibody infusions. Then, pentylenetetrazol (PTZ) was administered intraperitoneally to evaluate seizure susceptibility. Immunohistochemistry processed for assessment of hippocampal astrocyte proliferation and expression intensity of target NMDAR and LGI1 antigens.Results: No spontaneous activity was observed during the antibody infusions. PTZ-induced seizure stage was significantly higher in the NMDAR-IgG and LGI1-IgG groups compared to control. Besides, memory deficits were observed in the NMDAR and LGI1-IgG groups. We observed enhanced astrocyte proliferation in NMDAR-and LGI1-IgG groups and reduced hippocampal NMDAR expression in NMDAR-IgG group.Significance: These findings suggest that neuronal surface auto-antibody administration induces seizure susceptibility and disturbed cognitive performance in the passive transfer rat model of LGI1 AE, which could be a potential in-vivo model for understanding immune-mediated mechanisms underlying epileptogenesis and highlight the potential targets for immune-mediated seizures in AE patients.